Design Improvement Of Fixable Clamping Jig For Milling Machine Based On Surface Roughness - Ab Wahab, Norfariza; Onn, Azizi Arif; Nordin, Abd Khahar; Zahari, Madiha; Abd Mutalib, Nurliyana; Mohd Nor, Rozilawati; Md Nasir, Nur Syuhada (Asian Research Publishing Network (ARPN), 2020)
Jigs provide a means of manufacturing interchangeable parts since they establish a relation with predetermined tolerances, between the work and the cutting tool. Jigs are used on drilling, reaming, tapping, milling and tapping. The objective of this project is optimizing and analyse of the fixable clamping jig for milling machine. The method is modified clamp mechanism of the previous jig, optimize the design of the fixable clamping jig for milling machine, and analyse the result of fixable clamping jig in term of surface roughness. The result of the experiment will be evaluated base of surface roughness by using Portable Surface Roughness Tester, SJ-401. Then, the result will compare with current vise result and fixable clamping result. From the results that have get, the average of Ra value using current vise as a clamping method is higher than using fixable clamping as a clamping method which are 3.468 when using current vise and 1.657 when using fixable clamping for Delrin as a work piece. While for aluminum as a work piece, the average of Ra value using current vise as a clamping method is lower than using fixable clamping as a clamping method using current vise is 3.069 compared to using flexible clamping is 5.908